Strategy to Strengthen Unumart's Performance through the Role of Digital Payment Optimization in the First Quarter of 2025 - Faiqoh, Dina Nadiyah; Putri, Sastya; Kurniawan, Denny; Setyowati, Reni Diah; Sivi, Nuari Anisa (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
Digital transformation emphasizes digitalization as a strategy for enhancing efficiency and competitiveness. The shift to tech-based payment systems, like QR Codes and e-wallets, simplifies transactions, boosting operational efficiency and potential sales for businesses. This study aims to empirically test the effect of Digital Payments (QRIS) on UNU Mart Performance (Sales). This study is a causal research with quantitative methods. The examples obtained through purposive sampling techniques, from 90 data only 70 can be processed during the first 3 months of 2025, using primary data from the UNU Mart cashier application. In this study, SPSS statistical software version 24 was used. The results of the study showed that the variables taken, namely QRIS on Sales, were proven to have a positive and significant effect. In addition, seen from the multiple correlation, more than 50% of QRIS variables affect Sales.